El teatro de los siglos de oro y sus influencias temáticas en El esclavo del demonio de Antonio Mira de Amescua - Despain, Elisabeth, author; Suárez García, José Luis, advisor; Leal, Francisco, committee member; Ehlers-Zavala, Fabiola P., committee member (Colorado State University. Libraries, 2010)
The daily life of the Spanish golden age, with its history, society, and socioeconomic problems, presents itself in a particular genre of theater produced during this era. The Baroque theater breaks the Aristotle formula used until this time, and defines the Spanish comedy as the voice of the people. Antonio Mira de Amescua's El esclavo del demonio is a clear representation of this style. It addresses the topics of honor and religion, two popular topics among the Spanish people during the Baroque period, through the ancient theme of selling your soul to the devil. This topic has been used in literature at different times, including Goethe's Faust two centuries later. El esclavo del demonio has the polished form and content for the Baroque literature enthusiast.
Spanish theatre from the Golden Age and its thematical influences in the Devils slave ty Antonio Mira de Amescua
Department Head: Paola Malpezzi Price.
Text in Spanish; title and abstract in English and Spanish.